A Middle-Aged Woman with Logopenic Progressive Aphasia as a Precursor of Alzheimer's Disease: Case Report and Review of the Literature - Stephanie M. Awad; Amer M. Awad (Case Reports in Neurological Medicine)
Primary progressive aphasia is a neurodegenerative disorder that was recently classified into three types: fluent (semantic), nonfluent, and logopenic. The logopenic variant is the least common one and is closely related to Alzheimer's disease in comparison to the other two variants that are closely related to frontotemporal dementia. We report the case of a middle-aged woman who presented to our center with progressive aphasia that was undiagnosed for two years. The patient's neurological evaluation including positron emission tomography is consistent with a logopenic variant of primary progressive aphasia.